b3 - 5b2 + 12 = (b - 2)(b2 - 3b - 6)Check:(b - 2)(b2 - 3b - 6)= b(b2 - 3b - 6) - 2(b2 - 3b - 6)= b3 - 3b2 - 6b - 2b2 + 6b + 12= b3 - 5b2 + 12
The other factor is 1.
12(m + 5)
12(b + 1)(b + 1)
(x + 6)(x + 2)
It is: 4(x+3)
3(4 + q)
3(3z + 4)
You can factor it, if you consider that simpler.
The GCF of 2x and 12 is 2.
Assuming the question is written as: x2+11x-12 This would factor to: (x+12)(x-1)
There is no factor of the expression in the question.
(7x - 12)(7x - 12) or (7x - 12)2
It is (x+3)(x+4) when factored
12x^2+24x+12 12(x^2+2x+1) 12(x+1)^2
First lets set up the equation.12 - 7b + 10b = 18.Now lets combine all like terms on the left hand side.12 - 7b + 10b = 1812 + 3b = 18Now lets combine all like terms using the like terms on the left side and on the right side.12 + 3b = 18-12 -123b = 6Now lets divided (since the 3 is being multiplied to the b).3b/3 = 6/3So your final answer is:b = 2
=3x * * * * * The correct answer is: x2 + 7x + 12 = (x + 3)(x + 4).
y^2 + 7y + 12 = (y+4)(y+3)
The GCF is 4.